Suspended sediment transport estimation in Negro River (Amazon Basin) using MSI/Sentinel-2 data - Marinho, Rogério Ribeiro; Filziola, Naziano Pantoja; Martinez, Jean-Michel; Harmel, Tristan (Revista Brasileira de Geomorfologia, 2022)
The dynamics of suspended sediment production and transport in large rivers are essential geomorphological processes that can influence biodiversity. The aim of this work was to analyze the spatio-temporal variation of suspended sediment transport in the lower Negro River using Sentinel-2 images. The suspended sediment concentration (SSC) was estimated from the reflectance of band 4 of the MSI sensor onboard the Sentinel-2A and Sentinel-2B. The results indicate that the hydrological regime controls the temporal variability of SSC, being higher in the low water period and lower during flooding, with a mean concentration of 5.28 mg L-1 for the period 2015–2019. Analysis of the spatial variation of SSC in Sentinel-2 images indicated a zone of active sediment deposition located downstream of the islands of the Anavilhanas Archipelago. Geology, forest cover, and hydrological variability are the main factors controlling the low sediment yield of the basin, with an estimated suspended solid flux of 5.76×106 ton∙year-1 and a specific yield of 8 ton∙km-2∙year-1. Despite the lower quantity of images between February and April, due to high cloud cover, this study showed that Sentinel-2 images could be used to monitor the temporal and spatial dynamics of suspended sediment transport in Amazonian blackwater rivers.